THE RELATIONSHIP BETWEEN PRINCIPAL LEADERSHIP AND SCHOOL CLIMATE AND TEACHERS’ JOB SATISFACTION OF THE SPK SECONDARY SCHOOL IN PAMULANG, TANGERANG SELATAN - Sisilia Juni Arianti; Hotner Tampubolon; Tarsicius Sunaryo (Pascasarjana Universitas Kristen Indonesia Program Magister Administrasi/Manajemen Pendidikan, 2019)
Job satisfaction is an important issue when dealing with the teachers’ turn over in institution. Many factors influence teachers’ job satisfaction, among others are the principal leadership and the school climate. This research aimed to know the relationship between those factors. This research is a correlation study. The sample is the teachers in SPK Secondary School in Pamulang, Tangerang Selatan. Questionnaires were distributed to 32 respondents. It was found out that 1.) There was a very strong, positive and significant correlation between the teacher’s job satisfaction and the principal leadership, with the computed r = .890., 2.) There was a strong, positive and significant correlation between the teacher’s job satisfaction and the school climate, with the computed r = .795., and 3.) There was a very strong, positive and significant correlation between the principal leadership and the school climate to the teacher’s job satisfaction, with the computed r = .905. The findings showed that opportunity to develop, relationship between leaders and teachers, and sense of responsibility are the indicators that are very prominent in each variable. The conclusions are 1). The higher the principal leadership is, the higher the teachers’ job satisfaction will be., 2). The higher the school climate is, the higher the teachers’ job satisfaction will be., 3). The higher the principals leadership and the school climate are, the higher the teachers’ job satisfatiction will be. Providing adequate support facilities, training, and creating a more relax atmosphere are some recommendations for maintaining the teachers’ job satisfaction in that school